Analisis Pengaruh E-Commerce Terhadap Penjualan Item Di Koi-Ku Shop - Alan Darma Saputra Wijaya; I Gede Putu Krisna Juliharta; Ni Luh Putu Ning Septyarini Putri Astawa (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2023)
Today world trade is no longer limited by space and time. The high mobility of people who demand that the world of sales is able to provide services and goods instantly according to buyer requests. To overcome this problem, transactions arise using internet media to connect sellers. Transactions via the internet are better known as E-Commerce, so that with E-Commerce it can increase efficiency and effectiveness in sales by utilizing information technology, low prices considering that making a website on the internet is cheaper than opening retail outlets in various places, as well as through purchasing services. internet will continue with the delivery of goods to the buyer. The purpose of this research is to find out about the effect after the existence of E-Commerce on Item Sales at the Koi-ku Shop. The method used in this study is descriptive qualitative, where the population in this study is the Owner Koi-ku Shop.